2016
DOI: 10.1242/jcs.193037
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis is required for axonal growth

Abstract: During early development, neurons undergo complex morphological rearrangements to assemble into neuronal circuits and propagate signals. Rapid growth requires a large quantity of building materials, efficient intracellular transport and also a considerable amount of energy. To produce this energy, the neuron should first generate new mitochondria because the pre-existing mitochondria are unlikely to provide a sufficient acceleration in ATP production. Here, we demonstrate that mitochondrial biogenesis and ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Finally, we tested whether the above‐described changes are sufficient to affect neuronal ATP levels and survival. We first estimated neuronal ATP/ADP ratio using the genetically encoded fluorescent ratiometric probe Perceval HR, which we have shown to be sufficiently sensitive to track intracellular ATP/ADP ratio in our model (Vaarmann et al , ). Glutamate treatment induced a clear and significant decrease in ATP levels that was reversed by the Miro1 EF and augmented by the Miro1 WT (Fig I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we tested whether the above‐described changes are sufficient to affect neuronal ATP levels and survival. We first estimated neuronal ATP/ADP ratio using the genetically encoded fluorescent ratiometric probe Perceval HR, which we have shown to be sufficiently sensitive to track intracellular ATP/ADP ratio in our model (Vaarmann et al , ). Glutamate treatment induced a clear and significant decrease in ATP levels that was reversed by the Miro1 EF and augmented by the Miro1 WT (Fig I).…”
Section: Resultsmentioning
confidence: 99%
“…Neuronal somas expressing the ATP/ADP ratio sensor Perceval HR were excited using a 405‐nm diode laser and a 488‐nm line of an Argon laser, and emission was collected using a 494–553‐nm window (Vaarmann et al , ). Data are expressed as the ratio of fluorescence emission from neuronal soma evoked by 488 nm excitation/405 nm excitation (F488 nm/F405 nm).…”
Section: Methodsmentioning
confidence: 99%
“…In neurons, proper calcium homeostasis is required for gene transcriptional regulation. After excitatory neuronal stimulation, NMDAR activation leads to synaptic Ca 2+ influx, which in turn activates the kinase CAMKII and transcription factors such as cyclic AMP response element‐binding protein (CREB) or PGC‐1a (Cohen et al, ; Vaarmann et al, ). Activated transcription factors then recruit epigenetic machinery to modulate their target gene expression, among them synaptic plasticity genes.…”
Section: Proposed Mechanisms Leading To Epigenetic Alterations In Thementioning
confidence: 99%
“…In the present study, elongated mitochondria were observed in neuritelike structures after neuronal differentiation of SHED. Mitochondrial localization in axons and local ATP production were required for the events of neuronal outgrowth, including growth corn motility and cytoskeletal assembly (Bernstein and Bamburg, 2003;Morris and Hollenbeck, 1993;Ruthel and Hollenbeck, 2003;Vaarmann et al, 2016). In addition, elongated mitochondria have been observed in the neurites of cortical neurons during neuronal differentiation (Cho et al, 2014).…”
Section: Discussionmentioning
confidence: 99%